Rancang Bangun Sistem Kontrol Penetas Telur Ayam Kampung Menggunakan Metode MADM dan SMS Gateway - Tijaniyah; Honainah (FT- UNDAR, 2019)
The process of good egg incubation is a major factor in the quality of native chicken eggs which during this time the native chicken mother has many problems such as the lack of eggs that hatch, the number of chickens that are not weather resistant so many eggs that do not hatch and chicken seeds in dead eggs, at least chicken breeders which incubates the eggs, there is no proper method in calculating the temperature and humidity parameters of the chicken coop and there is no information on the process of hatching eggs to farmers in real time. Overcoming this problem, the latest technology is needed that can replace the conventional system of farmers with a controlled system of chicken egg incubators. In this case, the author will make a machine equipped with a chicken hatching control system using the MADM calculation method and SMS Gateway technology as a medium of information to farmers.